Path Dependence, Competition, and Succession in the Dynamics of Scientific Revolution - Sterman, John D.; Wittenberg, Jason (Organization Science, 1999)
What is the relative importance of structural versus contextual forces in the birth and death of scientific theories? We describe a formal dynamic model of the birth, evolution, and death of scientific paradigms based on Kuhn's Structure of Scientific Revolutions. The model represents scientific activity as a changing set of coupled institutions; a simulated ecology of interacting paradigms in which the creation of new theories is stochastic and endogenous. The model captures the sociological dynamics of paradigms as they compete against one another for members, solve puzzles, and recognize anomalies. We use sensitivity tests and regression to examine the role of intrinsic versus contextual factors in determining paradigm success. We find that situational factors attending the birth of a paradigm largely determine its probability of rising to dominance, while the intrinsic explanatory power of a paradigm is only weakly related to the likelihood of success. For those paradigms surviving the emergence phase, greater explanatory power is significantly related to longevity. However, the relationship between a paradigm's “strength” and the duration of normal science is also contingent on the competitive environment during the emergence phase. Analysis of the model shows the dynamics of competition and succession among paradigms to be conditioned by many positive feedback loops. These self-reinforcing processes amplify intrinsically unobservable microlevel perturbations in the environment—the local conditions of science, society, and self faced by the creators of a new theory—until they reach macroscopic significance. Such path dependent dynamics are the hallmark of self-organizing evolutionary systems. We consider the implications of these results for the rise and fall of new ideas in contexts outside the natural sciences such as management fads.